miR-155 Contributes to the Immunoregulatory Function of Human Mesenchymal Stem Cells - Pers, Yves-Marie; Bony, Claire; Duroux-Richard, Isabelle; Bernard, Laurène; Maumus, Marie; Assou, Said; Barry, Frank; Jorgensen, Christian; Noël, Danièle (Frontiers in Immunology, 2021)
Objectives: Mesenchymal stem/stromal cells (MSCs) are widely investigated in regenerative medicine thanks to their immunomodulatory properties. They exert their anti-inflammatory function thanks to the secretion of a number of mediators, including proteins and miRNAs, which can be released in the extracellular environment or in the cargo of extracellular vesicles (EVs). However, the role of miRNAs in the suppressive function of MSCs is controversial. The aim of the study was to identify miRNAs that contribute to the immunomodulatory function of human bone marrow-derived MSCs (BM-MSCs). Methods: Human BM-MSCs were primed by coculture with activated peripheral blood mononuclear cells (aPBMCs). High throughput miRNA transcriptomic analysis was performed using Human MicroRNA TaqMan® Array Cards. The immunosuppressive function of miRNAs was investigated in mixed lymphocyte reactions. Results: Upon priming, 21 out of 377 tested miRNAs were significantly modulated in primed MSCs. We validated the up-regulation of miR-29a, miR-146a, miR-155 and the down-regulation of miR-149, miR-221 and miR-361 in additional samples of primed MSCs. We showed that miR-155 significantly reduced the proliferation of aPBMCs. Analysis of miRNA-mRNA interactions revealed miR-221 as a potential target gene that is down-regulated by miR-155 both in primed MSCs and in aPBMCs. Conclusion: Here, we present evidence that miR-155 participates to the immunosuppressive function of human BM-MSCs and down-regulates the expression of miR-221 as a possible inflammatory mediator.